Governance Structure, CEO Attributes, and Profit Efficiency of listed securities Firms in Vietnam: New Evidence on Gender Diversity and Board Independence - Nguyen, Thi Lam Anh; Le, Thi Bich Ngan; Luong, Minh Ha (International Journal of Economics and Financial Issues, 2025)
This study examines the impact of board and CEO characteristics on the profit efficiency of securities companies in a developing market context. Using panel data of 35 listed securities companies in Vietnam during the period–2015-2023 and applying the Feasible Generalized Least Squares (FGLS) method, this study provides new evidence on the governance-performance nexus in the securities sector, which is characterized by high volatility and strong competition. The results indicate that securities firms with female CEOs and a higher ratio of independent directors demonstrate lower profit efficiency levels, while a higher participation of female members on the board of directors significantly impacts firm outcomes. Further analysis shows that the beneficial impact of female directors reduces as firms grow larger, suggesting potential constraints on women’s influence in larger organizations. In addition, the adverse effect of board independence is reduced in companies that are larger, have a higher level of foreign ownership, a higher leverage ratio, and during the COVID-19 pandemic. Based on the results, this study provides practical recommendations for regulators and securities firms to strengthen board structures, promote effective female participation, and enhance governance mechanisms tailored to firm-specific and external conditions.